(untitled) (Global Journal of Management and Business Research, 2014)
The attitude to work of the Nigerian worker has been a subject of criticism among scholars and other interested parties for sometime now. The non-challant attitude to work of the Nigerian worker is independent of geopolitical divisions, rural urban residence, religious affiliation, sex and age. Nigerians generally have a poor attitude to work. Like most other general statements, the one about attitude to work in this country may be true without necessarily being an accurate assessment of the situations. Attitudes are characterized by a predisposition or state of readiness to act or react in a particular way to certain stimuli; based on the understanding that they are relatively stable attitude of workers thus become very important to management in the discharge of their responsibilities and formulation of policies. Accountability, which has often been stressed should be given its due attention. This paper is focused on the attitude to work by Nigerians Workers.